A microfluidic coculture model for mapping signaling perturbations and precise drug screening against macrophage-mediated dynamic myocardial injury - Zhao Gao; Zhiyong Du; Yu Hou; Kun Hua; Pengfei Tu; Xiaoni Ai; Yong Jiang (Acta Pharmaceutica Sinica B)
Macrophage-mediated inflammation plays a pivotal role in cardiovascular disease pathogenesis. However, current cell-based models lack a comprehensive understanding of crosstalk between macrophages and cardiomyocytes, hindering the discovery of effective therapeutic interventions. Here, a microfluidic model has been developed to facilitate the coculture of macrophages and cardiomyocytes, allowing for mapping key signaling pathways and screening potential therapeutic agents against inflammation-induced dynamic myocardial injury. Through metabolic profiling and bioinformatic enrichment analysis, the microchip model with dynamic cell-cell crosstalk reveals robust activation of inflammatory and oxidative stress-associated metabolic pathways, closely resembling metabolic profiles of myocardial infarction in both humans and rodents. Furthermore, an integrative screening strategy has been established to screen bioactive natural products precisely, identifying ginsenoside Rb1 and protocatechualdehyde as promising cardioprotective candidates in vitro and in vivo. Taken together, the microfluidic coculture model advances mechanistic insight into macrophage-mediated cardio-immunology and may accelerate the discovery of therapeutics for myocardial injury.